IgG4-related disease with elevated adenosine deaminase in pleural effusion diagnosed clinically using thoracoscopy under local anesthesia and FDG-PET-CT. (2020) - Tamura, Kentaro; Suzuki, Manabu; Ishii, Satoru; Takasaki, Jin; Naka, Go; Iikura, Motoyasu; Izumi, Shinyu; Takeda, Yuichiro; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: In general, we have to assume tuberculous pleurisy when a patient presents with pleural effusion and elevated adenosine deaminase (ADA). However, other diseases need to be considered, including immunoglobulin (Ig)G4-related disease (IgG4-RD). This case involved a 65-year-old asymptomatic man with right pleural effusion showing elevated ADA. He had no articular findings or rashes. Results were negative for all autoantibodies. Pleura, mediastinal lymph nodes, and areas around the aorta and vertebra showed high uptake of 18 F-fluorodeoxyglucose (FDG) on positron-emission tomography-computed tomography (PET-CT). These findings were specific for IgG4-RD. Based on the results of FDG-PET-CT, we performed thoracoscopy under local anesthesia and bronchoscopy. Pleural biopsy and culture, and other examinations including sputum and blood yielded negative findings for tuberculous pleurisy. A pleural biopsy specimen showed IgG4-positive plasma cells and fibrosis without obliterative phlebitis or storiform fibrosis, and serum IgG4 was also high. The ratio of IgG4-to IgG-positive plasma cells was under 40%, and >10 IgG4-positive cells were seen in high-power fields. This case was classed as 'possible IgG4-RD' on the comprehensive diagnostic criteria for IgG4-RD, but did not meet the diagnostic criteria for IgG4-related respiratory disease. Prednisolone proved effective against the pleural effusion. We therefore clinically diagnosed IgG4-RD with pleural effusion based on the 2019 classification criteria for IgG4-RD in the United States. Although few cases of IgG4-RD with pleural effusion have been reported, this disease needs to be considered among the differential diagnoses for high-ADA pleural effusion. FDG-PET-CT and thoracoscopy under local anesthesia may be helpful for diagnosis. Highlights: ImmunoglobulinG4-related disease (IgG4-RD) with pleural effusion is rare. We should assume IgG4-RD as one of the differential diagnoses of pleural effusion with high level of adenosine deaminase. Thoracoscopy under local anesthesia and 18F-Fluorodeoxyglucose positron emission tomography-computed tomography (FDG-PET-CT) may be useful as an adjunctive tool for making a diagnosis of IgG4-RD. We could diagnosed as IgG4-RD with pleural effusion based on findings of FDG-PET-CT and thoracoscopy, and the responsiveness to prednisolone.